"Ecclesiae" y "monasteria" en la documentación latina de León: un paisaje monumental - Reglero de la Fuente, Carlos M.; Pérez Rodríguez, Estrella (Turnhout: Brepols, 2018)
Ecclesia y monasterium son dos términos fáciles de traducir ("iglesia" y "monasterio"), pero difíciles de definir en la Edad Media leonesa. Pueden designar una misma realidad o distinguir dos elementos de la misma. Ecclesia conservaba su significado etimológico de "asamblea de la comunidad de fieles cristianos, vivos y difuntos", pero también se aplicaba a las distintas subdivisiones de esta comunidad: la de cada reino, diócesis, parroquia, e incluso a la comunidad de monjes que habitaban un monasterio, a su convento. A lo largo de la Alta Edad Media esta ecclesia se fue petrificando e institucionalizando, como señala Iogna-Prat, de modo que la mayoría de las iglesias que aparecen en la documentación son edificios destinados al culto, a la vez que propietarias jurídicas de una serie de bienes y derechos. No se trata de tres significados diferentes, de límites claros, sino de un amplio campo semántico del que cada escritor utiliza una parte, a veces muy concreta, otras genérica. En su significado arquitectónico, la iglesia puede ser también llamada basílica, aula o templum, aunque cada una de estas palabras tiene sus matices. El monasterium era, en principio, una realidad diferente: arquitectónica (el conjunto de edificios en que habita una comunidad monástica), pero también institucional (la "persona jurídica" propietaria de bienes). Las fronteras se desdibujan porque esa comunidad, el conventus, es también una ecclesia, y porque ese conjunto arquitectónico tiene en la iglesia-edificio su elemento más destacado. Así cada monasterium tiene su iglesia-comunidad, que puede ser muy reducida, y su iglesia-edificio, sin por ello ser una iglesia o solo una iglesia. La confusión aumenta porque antes de la Reforma Gregoriana algunos monasterios funcionaban como sede de una parroquia o de una feligresía. Además del significado, se analizan las numerosas variantes gráficas de ambas palabras, dado que son dos de los términos más empleados en la documentación, y se estudia su empleo en la identificación de iglesias locales o monasterios.
Ecclesia and monasterium are simple to translate ("church" and "monastery") but difficult to define in the Latin texts of the Middle Ages in Leon. They can refer to the same thing or be used to distinguish two parts of a whole. Ecclesia conserved its etymological meaning of the assembly of the community of faithful christians, both living and dead, but it was also used to refer to the different subdivisions in this community (each kingdom, diocese, parish, and even the community of monks living in a monastery, the conventus). Throughout the High Middle Ages this ecclesia gradually carne to refer to the (stone) building and to the institution, as pointed out by Iogna-Prat. So most of the churches that appear in the documents are buildings used for worship, to celebrate mass and the sacraments, while also being legal owners of a series of lands and rights. It is not a question of three clearly different meanings, but of a wide semantic field. Each writer chooses either a particular part or uses it generically. The episcopal church is the community of faithful within the territory, the cathedral and the clerics therein, the owner of a domain, etc. In its architectural meaning, the church can also be called basilica, aula or templum, although each of these words has its own peculiarities. The monasterium was in principle a different reality referring to the set of buildings where the monastic community lived, as well as the institution. The differences become blurred because this community, the conventus, is also an ecclesia, and because the concrete church building is the most outstanding element of the monastery. So each monasterium has its church as community, which may be very small, and its church as building, which may not be just a church. The confusion is even greater since, before the Gregorian Reform, some monasteries were also the seat of a parish. In addition to the meaning, we also analyze the spelling variations of both words. They are two of the words most used in the documents, so it is not surprising that there are 28 different ways of spelling ecclesia (including ecclesia, eglesia or eclesia) and 20 of monasterium (mainly monesterium). However, most variations only appear in a single document and are the result of errata, but also of a poor knowledge of Latin. We also study their use to identify local churches or monasteries. In general, churches are defined by their dedication, the use of which gradually declined during the period under study, or, less commonly, by their place name or demonym. Cathedral churches often used the demonym (Legionensis ecclesia). In the case of the monasteries, the use of the adjective is marginal, except in the case of San Juan de Corias. The most frequent use is that the monastery is known by its dedication, which may be combined with the place name.
Keywords: Monasterios; Historia medieval; León